Satisfaction and Loyalty of Honda Motorcycle Consumers in Jember - Reiga Ritomiea Ariescy (Journal of Economics, Business, and Government Challenges, 2018)
This research aims to analyze the effect of price and product quality on satisfaction and loyalty of Honda motorcycle customers in Jember. The research design is confirmatory research. The research population is all customers of Honda motorcycles in Jember, and then researcher take 114 sample. Researcher take respondents used non-probability sampling techniques with purposive sampling approach. Analysis tool used Structural Equation Modeling (SEM). The results of this research prove that product quality has a significant effect on customer loyalty. Product quality also has a significant effect on customer loyalty. Price does not effect on customer satisfaction, but price has a significant effect on customer loyalty. Customer satisfaction has a significant effect on customer loyalty.